Descriptive model of mechanical characteristics of leg muscles in elite karate athletes measured by TMG method - Jeknic, V.; Toskic, L.; Koropanovski, N. (Serbian Journal of Sports Sciences, 2020)
The aim of this study was to investigate the neuromuscular response of knee flexor and extensor muscles using the tensiomyography (TMG) method and to compare the TMG characteristics between the dominant and non-dominant lower extremity in male karate competitors. Muscle mechanical properties were recorded from the rectus femoris (RF), vastus medialis (VM), vastus lateralis (VL), biceps femoris (BF) and semitendinosus (ST) muscles of both legs. Three TMG parameters were analysed: maximal displacement (Dm), contraction time (Tc), and delay time (Td). Dm and Td parameters of the measured muscles were not affected by the lower extremity dominance in karate athletes. The dominant leg demonstrated a higher Tc of the RF (p = 0.013) and lower Tc of the BF (p = 0.004) compared to the non-dominant leg. A higher Tc of the RF occurs because of the controlled nature of punches and kicks. A lower Tc of the BF is due to the specific requirements of the fighting stance and frequent external hip rotation in karate techniques.